Hybridity and Ambivalence Issues in Natalie Diaz’s Selected Poems: A Postcolonial Study - Novita Pinem (Paradigma Lingua, 2024)
This study aims to analyze issues of hybridity and ambivalence that occur among Native Americans. The object of this research is Natalie Diaz’s (2020) selected poems. The theory used to analyze this issue is taken from the theory of postcolonialism by Homi K. Bhabha (1994). This study uses a qualitative method because the analysis is presented in the form of an essay and the data collected is in the form of text and paragraphs. The results of this study indicate that the subject of the poet and the people around him as Native Americans show a picture of hybridity issues in the form of social status, morals, language, education, art, lifestyle, perspective, and buildings. Furthermore, the issue of ambivalence is found in the form of work, life behavior, use of language, security systems, and civilization.